2019
DOI: 10.7554/elife.50130
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a positive feedback loop drives centrosome maturation in fly embryos

Abstract: Centrosomes are formed when mother centrioles recruit pericentriolar material (PCM) around themselves. The PCM expands dramatically as cells prepare to enter mitosis (a process termed centrosome maturation), but it is unclear how this expansion is achieved. In flies, Spd-2 and Cnn are thought to form a scaffold around the mother centriole that recruits other components of the mitotic PCM, and the Polo-dependent phosphorylation of Cnn at the centrosome is crucial for scaffold assembly. Here, we show that, like … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 77 publications
3
80
1
Order By: Relevance
“…The mitotic-PCM scaffolding proteins Spd-2 and Cnn are specifically phosphorylated when they are recruited to centrioles to form the mitotic PCM (Alvarez Rodrigo et al, 2019;Conduit et al, 2014a). To test if these proteins were specifically phosphorylated at SAPs, we purified SAPs from unfertilised eggs and centrosomes from fertilised embryos and found that both the SAPand centrosome-associated fractions of Spd-2 and Cnn were similarly phosphorylated ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mitotic-PCM scaffolding proteins Spd-2 and Cnn are specifically phosphorylated when they are recruited to centrioles to form the mitotic PCM (Alvarez Rodrigo et al, 2019;Conduit et al, 2014a). To test if these proteins were specifically phosphorylated at SAPs, we purified SAPs from unfertilised eggs and centrosomes from fertilised embryos and found that both the SAPand centrosome-associated fractions of Spd-2 and Cnn were similarly phosphorylated ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The SAPs in both asl 1 and asl B46 eggs recruited Sas-4 at slightly elevated levels compared to WT, even when normalising to the amount of GFP signal in each SAP to compensate for the increased size of the SAPs in the asl B46 eggs ( Figure 7D). Strikingly, however, the asl 1 SAPs recruited essentially no detectable Spd-2 or Cnn-the main components of the mitotic PCM scaffold in flies (Alvarez Rodrigo et al, 2019;Conduit et al, 2014a)-and organised essentially no detectable MTs ( Figure 7C,E,F). This finding supports the previous conclusions that the ability to recruit mitotic PCM and organise astral MTs is essentially abolished in asl 1 mutant tissues (Bonaccorsi et al, 1998;Varmark et al, 2007).…”
Section: Journal Of Cell Science • Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrate systems, Cep192 is required for efficient centrosome maturation (Gomez-Ferreria et al, 2007; Zhu et al, 2008) and is phosphorylated by Aurora A to create PBD-binding sites that recruit PLK1; this promotes the mutual activation of both kinases to promote mitotic PCM assembly (Joukov et al, 2010, 2014). In flies and worms, Spd-2/SPD-2 (the fly/worm homologue of Cep192) is concentrated at centrioles and centrosomes and its phosphorylation also helps recruit PLK1 to the mitotic PCM so that it can phosphorylate Cnn/SPD-5 (Decker et al, 2011; Alvarez-Rodrigo et al, 2019). In fly embryos, Spd-2, Polo and Cnn have been proposed to form a positive feedback loop that drives the expansion of the mitotic PCM around the mother centriole (Conduit et al, 2014b; Alvarez-Rodrigo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In flies and worms, Spd-2/SPD-2 (the fly/worm homologue of Cep192) is concentrated at centrioles and centrosomes and its phosphorylation also helps recruit PLK1 to the mitotic PCM so that it can phosphorylate Cnn/SPD-5 (Decker et al, 2011; Alvarez-Rodrigo et al, 2019). In fly embryos, Spd-2, Polo and Cnn have been proposed to form a positive feedback loop that drives the expansion of the mitotic PCM around the mother centriole (Conduit et al, 2014b; Alvarez-Rodrigo et al, 2019). In this scenario, Spd-2 is initially recruited to centrioles and is phosphorylated during mitosis, allowing the Spd-2 to form a scaffold that can recruit other PCM proteins and that fluxes outwards from the mother centriole.…”
Section: Introductionmentioning
confidence: 99%